2005
DOI: 10.1890/04-0016
|View full text |Cite
|
Sign up to set email alerts
|

Aphids Alter the Community-Wide Impact of Fire Ants

Abstract: Positive species interactions have the potential to strongly influence the structure and dynamics of ecological communities, yet surprisingly few studies have documented their general importance. We tested the hypothesis that the mutualistic association between fire ants and aphids enhances the impact of fire ants on the herbivorous and predaceous arthropod community of cotton. We found that the presence of aphids attracted foraging fire ants onto cotton plants. This shift from ground to foliar foraging result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
148
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(156 citation statements)
references
References 36 publications
7
148
0
1
Order By: Relevance
“…For example, Eubanks (2001) found patchy distributions of the red imported fire ant (Solenopsis invicta) in agricultural systems of the South-eastern United States. He suggested that the presence of anttended, honeydew-excreting aphids explained much of this variation-a supposition that was later supported by manipulative experiments (Kaplan and Eubanks 2005). Similarly, our broad-scale surveys across the Samoan Archipelago showed that the patchy distribution of A. gracilipes was strongly, positively correlated with the dominance of EFN-bearing plants (Savage et al 2009).…”
Section: Effects Of Nectar Subsidies On Forager Recruitmentsupporting
confidence: 64%
“…For example, Eubanks (2001) found patchy distributions of the red imported fire ant (Solenopsis invicta) in agricultural systems of the South-eastern United States. He suggested that the presence of anttended, honeydew-excreting aphids explained much of this variation-a supposition that was later supported by manipulative experiments (Kaplan and Eubanks 2005). Similarly, our broad-scale surveys across the Samoan Archipelago showed that the patchy distribution of A. gracilipes was strongly, positively correlated with the dominance of EFN-bearing plants (Savage et al 2009).…”
Section: Effects Of Nectar Subsidies On Forager Recruitmentsupporting
confidence: 64%
“…and S. picea did not limit the colonization of berries, considering that other studies have shown species within these two genera have important effects on herbivores (Kaplan and Eubanks 2005;Philpott et al 2008). Low ant activity on coffee bushes with Crematogaster spp.…”
Section: Discussionmentioning
confidence: 72%
“…But the ants may also attack other herbivores (e.g., Harvey & Eubanks, 2004). Kaplan & Eubanks (2005) explored such interactions in cotton fields where the invasive fire ant Solenopsis invicta Buren tends cotton aphids, Aphis gossypii. These researchers found a positive correlation between ant and aphid numbers on cotton plants, and documented many adverse effects of ants on other arthropods.…”
Section: Positive Interactions Among Herbivores: Numbers Of Generalismentioning
confidence: 99%